State regulation in the context of external exposure: the economic aspects of country development - Chervyakova , Olga (Theory and Practice of Public Administration, 2019)
The article analyzes the factors of external influences on the economic aspects of a country’s development, among which, in particular: the transition from an industrial to a post-industrial (informational) society, in which the basic resource is information; a significant increase in the number of countries that use the market model of the economy; strengthening globalization and internationalization processes in the economy; loss of state control over internal processes in the economy; an increase in the number of institutions capable of influencing the economy regulation; the increase in the size and scale of the influence integration interstate associations leads to the deformation of the territorial and / or economic borders individual countries; expansion of the subjects list of international economic relations that can influence the state policy on the national economy regulation; substantial limitation of the state monopoly on the implementation the regulatory function; the relationship of the state and non-state institutions on a global scale. The factors of external influence on state regulation of the economy have both positive and negative consequences. One of the most significant negative consequences is the exacerbation of problems in the field of public finance. In recent decades, there has been a clear tendency to imbalance in national budgets, and this applies both to countries whose economies are only moving towards a market and highly developed countries. As a result, there is an increase in public debt and a partial loss of sovereignty in the implementation of state regulation of the national economy, since creditors receive additional levers of influence on internal economic processes within the country. The article proposes scientifically based approaches to state regulation of the economic sphere, which make it possible to integrate into the modern world space without additional risks.